Pengaruh Konflik, Beban Kerja Terhadap Stres Kerja di Lingkungan Kerja Sebagai Variabel Moderasi - Achmad Fahriansyah; Ezzah Nahrisah; Rizki Putra (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This study aims to determine work conflict and workload on work stres with a non-physical work environment as a moderating variable in the North Sumatra Education Office. The design of this research is to test regression with moderating variables by using an interaction test or often called Moderated Regression Analysis (MRA). Moderated Regression Analysis (MRA) or interaction test is a special application of linear multiple regression where the regression equation contains an interaction element (multiplication of two or more independent variables). In this study, the entire population was opened by 115 employees, while the sample was 95 employees at the North Sumatra Education Office. The results of this study indicate that the variables of work conflict and workload have a significant effect on work stres. Non-physical work environment variables as moderating variables that can strengthen the effect of work conflict and workload on work stres.